Factors Affecting Uptake of Human Papilloma Virus (HPV) Vaccination among in- School Adolescent Girls in Wakiso District, Central Uganda. - Zaitune Nanyunja (Student's Journal of Health Research, 2020)
Background:    Since 2008, the Human Papillomavirus (HPV) vaccination has been routinely recommended for pre-adolescents and adolescent girls in Uganda. The introduction of HPV vaccines represents a step forward in the primary prevention of cervical cancer and other HPV-related malignancies. This study examines the factors affecting the uptake of HPV vaccination among in-school adolescent girls in Wakiso district to generate information that can be used to improve the uptake of such critical services.   Methodology:   A cross-sectional analytical study was employed. Both quantitative and qualitative data were collected concurrently. Data were collected from secondary schools in Wakiso district, selected using cluster sampling. Semi-structured self-administered questionnaires were used to collect quantitative data while data from mothers in Wakiso were collected using In-depth interviews through group dialogue sessions. Data were analyzed using SPSS 16.0; characteristics of the sample were summarized by descriptive statistics   Results:   The findings indicate the HPV vaccination uptake rate as low as 9.2% among the In-school adolescent girls in the Wakiso district. 68.5% belonged to the age group 16-19 (older adolescents). 91.2% had already had vaginal sex and 90.4% had ever had any STI. In the bivariate analyses, five factors were presented to be statistically significant with a P<0.05, implying that these factors were associated with HPV vaccination. They included the occupation of the caretaker, education level of the caretaker, perceived susceptibility to HPV infections and cervical cancer, perceived benefits of HPV vaccination, and knowledge attributes regarding HPV and HPV infections.    Conclusion:    The Ministry of the health of Uganda and partners should offer ample orientation and training to all health workers and encourage them to disseminate information on HPV vaccination to all eligible adolescents and their caretakers in Wakiso district central Uganda.